2014
DOI: 10.1179/2049396714y.0000000078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of workplace exposure to respirable crystalline silica in Italy

Abstract: Background: Crystalline silica is a human carcinogen and its use is widespread among construction, mining, foundries, and other manufacturing industries. Purpose: To evaluate occupational exposure to crystalline silica in Italy. Methods: Data were collected from exposure registries and descriptive statistics were calculated for exposure-related variables. The number of potentially exposed workers was estimated in a subset of industrial sectors. Linear mixed model analysis was performed to determine factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…The main limitations of the SIREP database are the inhomogeneous territorial coverage and the underrepresentation of some economical activities, as already underlined in previous studies (27,28). Data collection and reporting for the SIREP system is under the responsibility of the employer, and we observed that the number of exposure measurements differed by industrial sector and firm size.…”
Section: Discussionmentioning
confidence: 59%
“…The main limitations of the SIREP database are the inhomogeneous territorial coverage and the underrepresentation of some economical activities, as already underlined in previous studies (27,28). Data collection and reporting for the SIREP system is under the responsibility of the employer, and we observed that the number of exposure measurements differed by industrial sector and firm size.…”
Section: Discussionmentioning
confidence: 59%
“…The International Agency for Research on Cancer (IARC) has classified crystalline silica as a known human carcinogen (9). The National Institute for Occupational Safety and Health (NIOSH) and the National Toxicology Program (NTP) also define crystalline silica as carcinogenic to humans (3,10).…”
Section: Introductionmentioning
confidence: 99%
“…The presence and quantity of free silica in mines and the occupational exposure of miners to silica dust have been the subject of many studies. Many of these studies have reported that, in most mines, the total and respirable dust levels are higher than the standard exposure limit (Golbabaei et al, 2004, Scarselli et al, 2014, Hayumbu et al, 2008, Azari et al, 2009. A study by Koo et al (2000) on the exposure to crystalline silica dust showed that the concentration of crystalline silica in the core-making unit was 0.023 mg/m 3 , which is lower than the limit, but in other units (molding, cleaning, melting) it was higher than the standard limits specified by the National Institute for Occupational Safety and Health (NIOSH) and ACGIH (Koo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%